The Effect of Aqueous Extract of Hibiscus sabdariffa seeds on Hematological Parameters of Anemic Rats - Reem Hassan Ahmed,; Abd Wahab Hassan Mohammed,; Hashim Mohammed El Hadi,; Mofida Yousif El khalifa, (International Journal of Phytomedicine, 2013)
The current study was conducted to investigate the effect of the aqueous extract of H. sabdariffa seeds on anemic rats. Anemia was induced in rats by two models, the first model is feeding rats with iron deficient diets for the induction of nutritional anemia while the hemorrhagic anemia model was induced in rats by bleeding off 30 % their blood volume. 400 mg of the extract/kg body weights of rats administered to anemic rats has increased their hematological parameters. This increase was significant in the hemoglobin, PCV and RBC count of hemorrhagic anemic rats and the extract caused significant increase in the hemoglobin level of the nutritionally iron-deficient rats.